Pengaruh Model Pembelajaran Kooperatif TipeBamboo DancingTerhadap Hasil Belajar pada Mata Pelajaran Komputer dan Jaringan Dasar Jurusan TKJ di SMKN 1 Kinali - Sari, Mita Purnama; Supriadi, Supriadi (Indonesian Research Journal on Education, 2023)
This research is motivated by the current basic computer and network learning outcomes where learning outcomes are below the Completeness Criteria. Problems that are found require a problem-based learning strategy that can help teachers in the delivery of learning materials, namely by asking students to solve a problem related to the subjectmatter so that students can be active in the learning process. This study aims to determine whether there is an "influence of cooperative learning type "bamboo dancing on learning outcomes" in computer subjects and basic networks at SMK N 1 Kinali.The type of research used is Quasi Experiment. The population in this study were students of class X of SMK N 1 Kinali for the academic year 2020/2021. Sampling was carried out using a purposive sampling technique, namely sampling with certain considerations. Thepopulation of class X is 61 students. Based on the results of the daily test (initial) the average class X TKJ 1 was used as the Experiment class, while some students from class X TKJ 3 were used as the control class.Based on the results of the analysisof the final test calculated using the t-test at a significance level of 0.05 obtained tcount = 2.259107766 and ttable = 2.020 and dk = 41. Because the value of tcount > ttable, it means that H0 is rejected and H1 received. Based on the above calculations,it can be concluded that tcount > ttable (2 .259107766 > 1.682) where H0 (No Effect of bamboo dancing cooperative learning on the results of Learning on computer and basic network subjects) is rejected, then Ha (There is Effect of cooperative learning bamboo dancing type on the results of Learning on basic computer and network subjects) accepted.